Pemetaan Penelitian seputar Variabel Determinan Return On Asset pada Perbankan Syariah: Studi Bibliometrik VOSviewer dan Literature Review - Muhammad Susandra Rohmandika; Eka Wahyu Hestya Budianto; Nindi Dwi Tetria Dewi (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2023)
This study aims to determine the development of research around Return On Asset/ROA in Islamic Banking. The research was conducted from 2011 to 2022, by searching national journals indexed by Sinta via the Garuda website, with the keyword “Return On Asset”. Based on the search results, there were 114 research articles, then inputted into the VOSviewer application and analyzed descriptively through a literature review study. The results showed that the number of publications had increased significantly every year. Furthermore, based on the results detected using the VOSviewer application, research related to Return On Asset/ROA is divided into 8 clusters and 123 items. Meanwhile, based on the results of a literature review study, there are 3 main themes related to Return On Asset/ROA in Islamic Banking.